Synergistic interaction between inorganic layered materials and intumescent fire retardants for advanced fire protection - Hu, Xiaochun (2022)
Intumescent fire-retardants (IFR) are widely applied in fire protection coatings of steel and wooden structures. The addition of inorganic fillers, such as layered ionic clays, can improve the fireproof performance of IFR coatings. However, a fundamental insight of how these filler materials synergistically interact with the IFR materials remains elusive. In this study, we address this fundamental knowledge gap by systematically investigating the synergy between the IFR fire protection coatings and the CaAlCO3-layer double hydroxide (LDH) or montmorillonite (MMT) fillers, which render substantially longer fire resistance (>20 min), reduced specific extinction area (by 54.7 and 44.1 m2 kg−2, respectively), and reduced heat release (by 0.9 and 0.7 MJ m−2, respectively). Combining experimental results and density functional theory calculations, we show for the first time that the superior fireproof performance of the MMT-IFR fire coating originates from the chemical modifications of the char layer by Si-doping. The chemical stabilisation of the silicon- and nitrogen-doped graphene (Si–N-G) structures improves the oxidation resistance of the char layer. Additionally, the formation of the Si–N-G structures with limited lattice deformation stabilised the porous morphology of the char layer, thereby promoting its heat-shielding performance.